Ladoga-Lake-Area Lambeosaurus Capture by A Falling Black Hole, and Its Re-Emergence Through Hydrated Lateral Extrusion, Explanation of The Scandinavian Peninsula and of the Finnish Lakes as Well as of the Low-Ob’s Delta and of the Novaya Zemlya - Pirot, Florent; Hejl, Ewald; Lavin, Claire (European Journal of Applied Sciences, 2023)
Two Lambeosauridae in a homosexual act were gobbled into the Earth by a small black hole descending along the axis of the Moon to the Earth. These animals killed into the mantle explain the shape of Scandinavia and of lakes in Central and Eastern Finland as well as topographical structures in Russia’s North. They were shattered into the small black hole and their bodies triggered rerise of corresponding structures explaining the peculiarities of the area in a topographical way and geological way as well, from the olivines of the Scandinavian Alps to the pattern of the Urals and of Novaya Zemlya. The construction from eruptive processes within the mantle explains also the still-ongoing counter-subsidence of the Turun Saaristo and of the Kvarken archipelagoes, altogether with oil reserves on the Norwegian side.